Efficacy of Direct Acting Antivirals (DAA) therapy in patients with recurrent hepatitis C after liver and kidney transplantation: a cross-sectional study - Kashani, Mehdi; Karimi, Mehdi; Sharifi Rayeni, Alireza; Azizi Nadian, Mohammad Ali; Mortezazadeh, Masoud; Parsaei, Amirhossein; Abolghasemi, Nooshin; Shirsalimi, Niyousha; Mofidi, Abbas; Seyyed Mahmoudi, Seyyed Taher (Frontiers in Medicine, 2024)
Background & objectives: Direct-acting antiviral (DAA) agents are now widely used to treat patients with hepatitis C infection (HCV) and effectively increase their sustained virologic response (SVR). However, the literature seems to lack or deficient evidence of DAA efficacy in more complicated patients, especially those with HCV reinfection after liver transplantation (LT) or liver-kidney (hepatorenal) transplantation (LKT). This study aimed to retrospectively evaluate the effectiveness of two different DAA regimens in LT and LKT patients with HCV reinfection.This cross-sectional study was conducted at three hospitals in Tehran, Iran, from 2014 to 2020, enrolling 53 patients with recurrent HCV infection after LT (n=35) or LKT (n=18). Patients were treated for 12 weeks with one of two DAA regimens: 37 patients (70%) received Daclatasvir and Sofosbuvir (SOF+DCV), while 16 patients (30%) received Sofosbuvir and Ledipasvir (SOF+LDV). Ribavirin (RBV) was added as an adjunct antiviral in 28 patients (52.8%). To assess the SVR, all patients were followed for 12 weeks after treatment.Results: Both DAA regimens were well-tolerated and effective, with 94.6% (35 of 37) achieving SVR-12 in the SOF+DCV group and 93.8% (15 of 16) in the SOF+LDV group.Additionally, SVR-12 rates were promising across treatment durations, with 93.9% (31 of 33) in the 12-week group and 95% (19 of 20) in the 24-week group achieving undetectable HCV RNA. No significant difference in SVR was observed between the two regimens (p=0.439).The DAA-based therapeutic regimen was well tolerated and showed significant effectiveness in achieving the virologic response in patients with HCV reinfection after LT or LKT.